(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2025)
Aim: to compare the difference of outcome from single dose versus multidose of prophylactic antibiotics use in elective herniotomy in children. Introduction: There are lot of studies to find out the role of using prophylactic antibiotics in clean surgery, but still there is controversies whether it is necessary or not for preventing post operative surgical site infection. Irrational use of antibiotics in surgery is a major problem in our country and it also increases the total treatment cost. This study will help our surgeons to take decision about the use of prophylactic antibiotic in clean surgery like herniotomy. Methodology: This prospective comparative study was conducted in the Department of Paediatric Surgery, Shaheed Ziaur Rahman Medical College Hospital, Bogura, Bangladesh. Results: Out of 100 patients of group A (single dose antibiotic) only four patients developed serous wound discharge (seroma 4%) and none of them developed wound infection. In 100 patients of group B (multiple dose antibiotic) single patient developed seroma and none of them developed wound infection. Conclusion: In this study we found that the difference of postoperative outcome in terms of surgical site infection between single dose versus multiple doses antibiotic use in herniotomy is minimum and statistically insignificant. We conclude that single dose antibiotic prophylaxis is sufficient in clean surgery like herniotomy that is also cost effective. Journal of Paediatric Surgeons of Bangladesh (2021) Vol. 12 (1 & 2): 37-40